Sexuality and the Filipina - Santiago, Lilia Quindoza 1949- (Quezon City University of the Philippines Press, 2007)
"This book marks significant moments in the evolution of gender relations, sexual practices, and notions of sexuality among Filipinos through a reading and re-reading of historical and literary texts from earliest times to the present. Subjugation to Spanish colonialism succeeded in demonizing many of these sexual practices so that today, behavior considered taboo are some ?moreThis book marks significant moments in the evolution of gender relations, sexual practices, and notions of sexuality among Filipinos through a reading and re-reading of historical and literary texts from earliest times to the present. Subjugation to Spanish colonialism succeeded in demonizing many of these sexual practices so that today, behavior considered taboo are some customs and rites which are deemed necessary and pleasurable by men and women among Philippine indigenous communities. The discourse in this book is a necessary first step in recuperating what could be a liberating sense of sexuality and gender relations especially for Filipinas in the modern-day world. It is hoped that the discussions will contribute to a sound and healthy discourse on gender and sexuality in the Philippines and finally lead to making sexuality a public discourse?one that can be lived, experienced, and narrated by the men, women, children, and the elderly all over the archipelago, whatever their sexual preferences or orientations."--Back cover.
Preface -- Introduction -- Chapter 1. Gender relations and sexuality among indigenous Filipinos -- Chapter 2. The body as colony : sexuality and colonization -- Chapter 3. Pepay : the female as subversive and revolutionary -- Chapter 4. Revolts from hymen : Filipinas writing the body and self -- Chapter 5. Sexuality and narrativity in the Philippine context -- Conclusion -- Selected narratives : myths and tales -- Short stories -- Testimonials and other narratives -- Afterword -- Bibliography -- Index.
In English, and some articles in Filipino.
In English, and some articles in Filipino.
UCWS-2014-G-1873 donated by U.P. Press.
Keywords: Sex role -- Philippines; Sex customs -- Philippines; Sex -- Philippines; Women -- Philippines -- Social conditions; Sex in literature; Women in literature